Lower serum brain-derived neurotrophic factor levels are associated with failure to achieve remission in patients with major depression after escitalopram treatment - Lee BH (Dove Medical Press, 2014)
Bun-Hee Lee,1 Young-Min Park,2 Tae Hyun Um,3 Sollip Kim3 1Department of Psychiatry, Gangnam Eulji Hospital, Eulji University, Seoul, 2Department of Psychiatry, 3Department of Laboratory Medicine, Ilsan Paik Hospital, Inje University College of Medicine, Goyang, South Korea Background: Remission, the primary goal of treatment for major depressive disorder (MDD), is the absence of significant signs or symptoms and the return to a state of normal functioning. A recent study found that the level of brain-derived neurotrophic factor (BDNF) increased after antidepressant treatment in remitted patients. This study evaluated serum BDNF levels in MDD patients with chronic maintenance treatment, and compared these between remission and nonremission groups.Materials and methods: Serum BDNF levels were measured in 34 MDD patients and 35 healthy controls. The severity of depression was measured using the Hamilton Depression Rating Scale (Ham-D). The MDD patients were divided into remission and nonremission groups according to a cutoff total Ham-D score of either ≤7 or ≤6.Results: Serum BDNF levels differed significantly between the remission, nonremission, and healthy control groups (P<0.05). The Bonferroni post hoc test confirmed that serum BDNF levels were significantly lower in the nonremission group than in the healthy-control group (P<0.05), but did not differ significantly between the remission and healthy-control groups.Limitations: This study included a small sample, and measured serum BDNF levels in the MDD patients at only one point during the maintenance treatment.Conclusion: This study found that serum BDNF levels during maintenance treatment were lower in MDD patients with failure to achieve remission than in controls, while the remitted subjects had normalized serum BDNF levels. A lower level of serum BDNF during maintenance treatment is associated with failure to achieve remission in patients with major depression. Moreover, serum BDNF levels after chronic antidepressant treatment can be used as a biological marker for detecting nonremission. Keywords: brain-derived neurotrophic factor, major depression, remission